Effect of modifiers for As, Cu and Pb determinations in sugar-cane spirits by GF AAS - Caldas, Naise Mary [UNESP]; Raposo, Jorge L. [UNESP]; Gomes Neto, José Anchieta [UNESP]; Barbosa, Fernando (Elsevier B.V., 2009)
Palladium plus magnesium nitrates with and without Ir, Ru and W were evaluated for the simultaneous determination of As, Cu and Pb in cachaca by graphite furnace atomic absorption spectrometry. For 20 mu L sample, 5 mu L Pd(NO(3))(2) and 3 mu L Mg(NO(3))(2) dispensed together onto the Ir-coated platform of the THGA, analytical curves in the 0-30.0 mu g L(-1) As, 0-1.50 mg L(-1) Cu and 0-60.0 mu g L(-1) Pb were built up and typical linear correlation coefficients were always better than 0.999. The limit of detection was 1.30 mu g L(-1) As, 140 mu g L(-1) Cu and 0.90 mu g L(-1) Pb. As, Cu and Pb contents in 10 cachaca samples agreed with those obtained by ICP-MS. Recoveries of spiked samples varied from 96% to 106% (As), 97% to 112% (Cu) and 92% to 108% (Pb). The relative standard deviation (n = 12) was typically 2.7%, 3.3% and 1.9%. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: As; Cu; Pb; Cachaca; Permanent modifier; GF AAS